(untitled) (Journal of Fiber Bioengineering and Informatics, 2016)
The expression ability of a commercial textile simulator was investigated by simulating textile images taking into account the effect of yarn count, weave density, yarn types and weave. The performance of the simulator was investigated by evaluating and comparing impressions of real textiles and simulated images. The effect of pattern and textile color on the simulation performance was also studied. It was found that simulated images of textiles with more complicated and multicolored patterns were perceived to be more alike to the real textiles. Simulated images with large patterns were also evaluated and found to compare favorably to real textiles. Color was observed to have no effect on the impression of simulated textile images. Therefore, textile simulation in the textile trade is more effective on complex variations of textile patterns and colors.